BIOCHEMICAL CONSTITUENTS AS STRESS INDICATORS IN FISHES - RAMALINGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
Certain tissue biochemical constituents serve as good indicators of stressors in animals (Le Resche et at., 1974). Transportation and exercise stress elevated the blood total carbohydrates of S. mossambicus. Similarly, toxic stress due to endosulfan caused hyperglycemic and hyperlactemic responses. The changes in the liver and muscle carbohydrate components and proteins during toxic stress revealed their usage in meeting the toxicity mediated energ demand.